(بناء وتطبيق مقياس الأمنيات لدى طفل الروضة) (Journal of the College of Basic Education, 2024)
The researchers followed the procedures by which they completed the current research and included the exploratory sample, which consisted of (100) male and female children in equal numbers between males and females. Its original sample consisted of (30) male and female children in equal numbers between the sexes. The research included two approaches: the experimental approach and the descriptive approach. Procedures for constructing the scale, procedures for their validity, reliability, and final application. The numerical results were subjected to statistical treatments according to statistical methods. The results revealed that there was an effect in the current study according to the wishes scale designed in it.The current research was limited to the following limits:1.Children in the pre-school stage (KG2), i.e. aged (5-6) years.2. Kindergartens in Baghdad Governorate / Rusafa II.3. Academic year (2023-2024)